"Can't We Just Have Some Sazón?" Student, Family, and Staff Perspectives on a New School Food Program at a Boston High School. (April 2016) - Chatterjee, Avik; Daftary, Genevieve; Campbell, Meg; Gatison, Lenward; Day, Liam; Ramsey, Kibret; Goldman, Roberta; Gillman, Matthew W.
ABSTRACT: BACKGROUND: In September 2013, a Massachusetts high school launched a nutrition program in line with 2013 United States Department of Agriculture requirements. We sought to understand attitudes of stakeholders toward the new program. METHODS: We employed community‐based participatory research methods in a qualitative evaluation of the food program at the school, where 98% of students are students of color and 86% qualify for free/reduced lunch. We conducted 4 student (N = 32), 2 parent (N = 10), 1 faculty/staff focus group (N = 14), and interviews with school leadership (N = 3). RESULTS: A total of 10 themes emerged from focus groups and interviews, in 3 categories—impressions of the food (insufficient portion size, dislike of the taste, appreciation of the freshness, increased unhealthy food consumption outside school), impact on learning (learning what's healthy, the program's innovativeness, control versus choice), and concerns about stakeholder engagement (lack of student/family engagement, culturally incompatible foods). A representative comment was: "You need something to hold them from 9 to 5, because if they are hungry, McDonald's is right there." CONCLUSION: Stakeholders appreciated the educational value of the program but stakeholder dissatisfaction may jeopardize its success. Action steps could include incorporating culturally appropriate recipes in the school's menus and working with local restaurants to promote healthier offerings.